TRAINING IN CREATING A DATABASE FOR STORING AND MANAGING SCHOOL DATA - Agus Iskandar; Gatot Soepriyono (Adisam Publisher, 2024)
In the current digital era, managing school data efficiently and effectively is crucial to supporting the learning and administration process. The background to this initiative is rooted in the need to store, access and manage school data in a more structured and systematic way. Problems often faced include limitations in storage capacity, difficulties in accessing data quickly, and challenges in ensuring data security. To overcome this, the proposed method is database creation training which is designed to provide an in-depth understanding of basic database principles, effective database design, as well as data management and security techniques. The aim of this training is to equip school staff and administrators with technical skills in building and managing school databases, so as to increase operational efficiency and ensure the integrity and security of educational data. This will enable schools to utilize information technology to better manage information resources, support strategic decisions, and improve the quality of education.